Cannabis cultivation and detection: A comparative study of Belgium, Finland and Denmark. (June 2013) - Athey, Nicholas C.; Bouchard, Martin; Decorte, Tom; Frank, Vibeke Asmussen; Hakkarainen, Pekka
<x xml:space="preserve">Abstract</x> Research on cannabis cultivation has identified several factors associated with a grower's likelihood of detection by law enforcement. However, these studies are difficult to compare, as they drew from different data sources and methods, and have focused on only one geographical location. This article revisits the issue of detection using a large sample of cannabis cultivators recruited in three countries: Belgium (n = 659), Denmark (n = 560) and Finland (n = 1296). Respondents were recruited in the context of a self-reported online survey conducted successively in each country between 2006 and 2008. Multivariate analyses suggest several country-specific similarities and differences. Importantly, the Finnish growers reported being arrested significantly more often than Belgians or Danes. The probability that Finnish growers would be arrested increased with time spent on growing, the size of the cultivation site and when respondents did not work alone. In Denmark, the risks increased with the size of the cultivation-related network, but decreased when respondents started growing later in life. In Belgium, no cultivation-related characteristics were associated with detection. The results indicate that the risks of apprehension for cannabis cultivation are typically country-specific. These findings are discussed in the context of country-specific policies in regards to cannabis.